2007
DOI: 10.1016/j.biosystems.2007.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Complex systems biology approach to understanding coordination of JAK-STAT signaling

Abstract: In this work, we search for coordination as an organizing principle in a complex signaling system using a multilevel hierarchical paradigm. The objective is to explain the underlying mechanism of Interferon (IFN γ ) induced JAK-STAT (specifically JAK1/JAK2-STAT1) pathway behavior. Starting with a mathematical model of the pathway from the literature, we modularize the system using biological knowledge via principles of biochemical cohesion, biological significance, and functionality. The modularized system is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Our results show that a combination of positive and negative feedback loops, together with the eventual degradation of the IFN signal in the medium, leads to a transient oscillatory response in several components of the pathway. This behavior is consistent with previous numerical results found in pure modeling studies [13], and goes beyond previous observations that indicate a simpler transient response [10,14,15]. We interpret the transient oscillatory response of the pathway in terms of the potential effectiveness of IFN-beta treatment in MS patients.…”
Section: Introductionsupporting
confidence: 92%
“…Our results show that a combination of positive and negative feedback loops, together with the eventual degradation of the IFN signal in the medium, leads to a transient oscillatory response in several components of the pathway. This behavior is consistent with previous numerical results found in pure modeling studies [13], and goes beyond previous observations that indicate a simpler transient response [10,14,15]. We interpret the transient oscillatory response of the pathway in terms of the potential effectiveness of IFN-beta treatment in MS patients.…”
Section: Introductionsupporting
confidence: 92%
“…Tyr985-phosphorylated STAT-3 is separated from lepRb, dimerizing and entering the nucleus. STAT-3 dimers, as a transcription factor, adjust the expression of targeting genes such as suppressor of cytokine signalling 3 (SOCS3) and neuropeptides [65][66][67]. There is another way to mediate JAK2 signalling: after leptin stimulation of lepRb phosphorylation on Tyr1077, a combination phosphoTyr1077 with the SH2 domain of STAT-5 allows STAT-5 phosphorylation and activation by JAK2 [68].…”
Section: Jak/stat Pathwaymentioning
confidence: 99%
“…The IFN related signaling pathways are very important and have attracted the attention of many researchers including some modelers (Beirer and Hofer, 2006;Li et al, 2009b;Sadler and Williams, 2008;Smieja et al, 2008;Soebiyanto et al, 2007;Taniguchi and Takaoka, 2001;Taniguchi and Takaoka, 2002;Yamada et al, 2003;Zi et al, 2005). In recent years, mathematical modeling and theoretic analysis were used to investigate the control mechanism and to identify the coordination of IFNinduced JAK-STAT signaling pathways (Beirer and Hofer, 2006;Smieja et al, 2008;Soebiyanto et al, 2007;Yamada et al, 2003;Zi et al, 2005). To our best knowledge, the modeling of signaling pathways of virus-mediated IFN induction has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 97%
“…However, it remains unclear if there exist potential antagonizing networks and a synergistic inhibitory effect from various proteins encoded by CSFV for antagonizing IFN-b induction. Many studies have demonstrated that system-level analysis of signaling pathways have the power to get new insights into cell signaling networks (Adler et al, 2006;Chou et al, 2008;Klipp et al, 2005;Li et al, 2009a;Liu et al, 2008;Zou et al, 2008a). The IFN related signaling pathways are very important and have attracted the attention of many researchers including some modelers (Beirer and Hofer, 2006;Li et al, 2009b;Sadler and Williams, 2008;Smieja et al, 2008;Soebiyanto et al, 2007;Taniguchi and Takaoka, 2001;Taniguchi and Takaoka, 2002;Yamada et al, 2003;Zi et al, 2005). In recent years, mathematical modeling and theoretic analysis were used to investigate the control mechanism and to identify the coordination of IFNinduced JAK-STAT signaling pathways (Beirer and Hofer, 2006;Smieja et al, 2008;Soebiyanto et al, 2007;Yamada et al, 2003;Zi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%